(untitled) (مجلة الواحات للبحوث والدراسات, 2022)
The emergence of covid-19 forced all Algerian universities to accelerate the adoption of e-learning through digital platforms to complete educational programs. In this study, we focused on Moodle platform in Ouargla University with a sample of (98) Management students. then we rely on the factors of the Technology Acceptance Model as a basic theory. To prove the hypotheses validity according to (TAM) theory, statistical tests were relied upon by calculating the arithmetic mean and standard deviation, in addition to a package of statistical tools. Spss 22.0. The results showed that the impact of TAM’s factors (perceived usefulness and intention towards usage) to use Moodle platform by students depends on the main and external factors, and statistical positive and strong relationship between these factors. Key words: Technology Acceptance Model, TAM, Moodle, platform, E-learning JEL classification: A20, O32.